2021
DOI: 10.1007/s11332-021-00791-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sitting time and physical activity on mental health during COVID-19 lockdown

Abstract: Objective The primary aim of this study was to investigate the association between physical activity (PA) and sitting time on adults’ mental health (i.e., depression, anxiety and wellbeing) and the influence of mediators and confounders. Methods An online survey was disseminated in the UK between May and June 2020. A total of 284 participants (33.5 ± 12.4 years) self-reported their PA, sitting time and mental health through validated questionnaires. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 80 publications
2
17
0
Order By: Relevance
“…The mixed-sex generalisability of our study is limited by the rather high sample size of females (72%). This is, however, similar to other investigations that have assessed sitting time and the effect on subjective wellbeing and mental health in the UK during the COVID-19 lockdown [13]. The sex distribution in the sample was not unexpected as research has suggested that females are more likely to respond to online research surveys than males [44], especially if the recruitment relies on convenient and snowballing methods.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The mixed-sex generalisability of our study is limited by the rather high sample size of females (72%). This is, however, similar to other investigations that have assessed sitting time and the effect on subjective wellbeing and mental health in the UK during the COVID-19 lockdown [13]. The sex distribution in the sample was not unexpected as research has suggested that females are more likely to respond to online research surveys than males [44], especially if the recruitment relies on convenient and snowballing methods.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, despite the containment strategies implemented, the New Zealand Government still encouraged participation in some form of physical activity (e.g., walking around the block) [9]. The effect of maintaining physical activity for mental health and subjective wellbeing during the COVID-19 lockdown has been explored in number of investigations [3,8,10,13]. Research has found that individuals who did not reach physical activity guidelines and engaged in more screen time during the COVID-19 containment restrictions had higher scores of depression and stress than those who exercised more during this pe-riod [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On average, people in the US, Canada and Germany spend 15–17 h per day indoors [ 4 ]. “Stay-at-home” restrictions, due to the COVID-19 pandemic, further decreased physical activity, having an adverse impact on mental health [ 5 ]. Lifestyle modifications and self-care practices can help patients to improve their health [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The negative effects of COVID-19 pandemic were decreased physical activity, increased screen time, sedentariness, weight gain, poor mental health, and financial problems. 1 2 3 4 5 6 7 COVID-19 restrictions affected vulnerable groups, such as people with physical or intellectual disabilities, more severely. 8 Over 90% reported a negative impact on mental health, and 61% reported a reduction in physical activity levels.…”
Section: Introductionmentioning
confidence: 99%